Integrating the Qur'anic worldview with the natural sciences: answering the call for Islamic secondary schools - Hassan, Nur Jannah (Springer, 2016)
The question of integration in the education of the ummah has been a top agenda among Islamic intellectuals and activists since the immediate postcolonial period, where secular humanism and atheistic modernism left Muslims with the legacy of a dichotomous education. Many contemporary Islamic educational institutions in the Muslim world have established since then, each with their somewhat distinctive modes of integration. How much have the Muslims progressed toward true integration of the Qur’ānic Worldview in the curricula of the natural sciences in secondary Islamic education, whose students are at critical stages of their cognitive, affective, spiritual, social and ethical developments? This article presents a qualitative report on the findings from field research that analused a few samples of integration models at a number of Islamic secondary schools in Malaysia and Indonesia; in relation to the ideal that integration constitutes a full merger an organic fusion between knowledge that is revealed and that which is acquired through reason. In an effort to understand Western modern science, this article briefly assesses the worldviews that have brought about the natural sciences to its current stage. It proposes a model for Islamic secondary education where the Natural Sciences undergo a discreet but holistic reconstruction, reinterpretation, and redirection from the framework of, and organically infused with the Qur’ānic worldview; whilst enriching ‘Islamic studies’ with a good grounding in and appreciation of the natural sciences.